Indecent proposal [videorecording (DVD)] - Jones, Amy Holden; Redford, Robert; Moore, Demi; Harrelson, Woody; Cassel, Seymour, 1935-2019; Platt, Oliver; Thornton, Billy Bob; Atherton, Howard; Barry, John, 1933-2011; Engelhard, Jack (Widescreen DVD collection., 2002)
A husband and wife can end their financial worries by accepting the offer of a billionaire for a million dollars in exchange for one night with the wife, but if they do, can their marriage survive?